Pengaruh Fee Audit, Kompetensi Auditor DanPerubahan Kewenangan Terhadap Motivasi AuditorStudi Empiris Pada KAP di Surakarta dan Yogyakarta - Aji, Esa Kharisma (2016)
This study aimed to test whether the effect on the audit fee motivation auditor, to test whether the effect on the auditor competence motivation auditor, to test whether the changes affect the motivation of the auditor's authority. This research is a quantitative survey method Population in this research is all public accountant / auditor of the level of partner, manager, senior, and junior registered and working in Public Accounting Firm (KAP) in Surakarta and Yogyakarta. The population in this study is the auditor who works at the office of public accountant Surakarta and Yogyakarta region registered diotoritas financial services. The following will explain roster KAP in Surakarta and Yogyakarta. The collection of data by using questionnaires, which will be filled or answered by the respondent auditor on Public Accounting Firm in Surakarta and Yogyakarta step in analyzing the data is the data of the respondents made tabulating the profile of respondents, after the test data quality, classic assumption test and test hypothesis with multiple linear regression analysis. Fee audit results showed a positive effect on the motivation of the auditor, proved the test results were gained tcount t> t table (3,986> 2,020) with a significance value of 0.000 <0.05 then the H1 is accepted. Competence auditor positive effect on motivation auditor, proved the test results were gained tcount t> t table (4,250> 2,020) with a significance value of 0.000 <0.05, the H2 is accepted. Changes negatively affect the authority of the auditor motivation, t-test results demonstrated that obtaining tcount> ttable (-3046 <-2.020) with a significance value of 0.004 <0.05, the H3 is accepted.